Millimeter methanol emission in the high-mass young stellar object G24.33+0.14. (5th September 2022) - Hirota, Tomoya; Wolak, Pawel; Hunter, Todd R; Brogan, Crystal L; Bartkiewicz, Anna; Durjasz, Michal; Kobak, Agnieszka; Olech, Mateusz; Szymczak, Marian; Burns, Ross A; Aberfelds, Artis; Baek, Giseon; et al.
Abstract: In 2019 September, a sudden flare of the 6.7 GHz methanol maser was observed toward the high-mass young stellar object (HMYSO) G24.33+0.14. This may represent the fourth detection of a transient mass accretion event in an HMYSO after S255IR NIRS3, NGC 6334I-MM1, and G358.93−0.03-MM1. G24.33+0.14 is unique among these sources as it clearly shows a repeating flare with an 8 yr interval. Using the Atacama Large Millimeter/submillimeter Array (ALMA), we observed the millimeter continuum and molecular lines toward G24.33+0.14 in the pre-flare phase in 2016 August (ALMA Cycle 3) and the mid-flare phase in 2019 September (ALMA Cycle 6). We identified three continuum sources in G24.33+0.14, and the brightest source, C1, which is closely associated with the 6.7 GHz maser emission, shows only a marginal increase in flux density with a flux ratio (Cycle 6/ Cycle 3) of 1.16 ± 0.01, considering an additional absolute flux calibration uncertainty of 10% . We identified 26 transitions from 13 molecular species other than methanol, and they exhibit similar levels of flux differences with an average flux ratio of 1.12 ± 0.15. In contrast, eight methanol lines observed in Cycle 6 are brighter than those in Cycle 3 with an average flux ratio of 1.23 ± 0.13, and the higher excitation lines tend to show a larger flux increase. If this systematic increasing trend is real, it would suggest radiative heating close to the central HMYSO due to an accretion event which could expand the size of the emission region and/or change the excitation conditions. Given the low brightness temperatures and small flux changes, most of the methanol emission is likely to be predominantly thermal, except for the 229.759 GHz (8−1 –70 E) line known as a class I methanol maser. The flux change in the millimeter continuum of G24.33+0.14 is smaller than in S255IR NIRS3 and NGC 6334I-MM1 but is comparable with that in G358.93−0.03-MM1, suggesting different amounts of accreted mass in these events.